The latent risk of iron deficiency during childhood period - Chandra, Dian Novita (Indonesian Nutrition Association, 2024)
Anaemia is a serious public health concern for Indonesian children under the age of five, with a prevalence of more than 20% according to the last national health survey in 2023. Iron deficiency accounts for over half of anaemia cases, causing delayed cognitive development, weakened immune systems, and poor overall health outcomes. Inadequate dietary intake, a poor socioeconomic level, and a high prevalence of infectious diseases exacerbate the situation, necessitating targeted nutritional therapy and public health initiatives to address this prevalent issue of iron deficiency anaemia (IDA).